O trabalho das (os) psicólogas (os) no SUAS : materializando a assistência social enquanto política social pública - Motta , Roberta Fin (2015)
This thesis brings up the insertion of Psychology in the public social assistance politics, particularly in Social Work, and more specifically, in the process of building the processes of the job that affects directly on the daily routine of the psychologists who work at SUAS (Social Assistance Care System), especially those who work at the CRASs (Social Assistance Reference Centers) connected to the FASC (Social Assistance and Citizenship Foundation) of Porto Alegre, Rio Grande do Sul, Brazil. This thesis is organized in three sections. The first section consists of a study about published academic production about Psychology in the Social Work in Brazil, with emphasis in its relationship with the CRASs. This draws a possibility to analyze the historical evolution of the researcher’s preoccupation regarding this issue, as well as observation of some basic characteristics of the productions. For this, a study took place inspired on a narrative review proposal with consultation of the electronic databases. In the second section, there is an attempt to characterize and discuss the work of the psychologists within the SUAS, more specifically of those working at the CRASs.This study parts from the premise that the psychologists are employed in the Social Assistance System, essential to the engineering and weaving of the politics, as well as being necessary to the users to warrant access to their social rights. The third and last section debates about the work processes and the practices of the psychologists. These last two studies are based on research analysys done with 27 professionals connected to CRASs, where data was collected through interviews and analysed with the help of Fundametal Theory (FT). The results obtained indicate that in the last years there has been an important involvement and investment in the Social Assistance area. Moreover, Social Assistance has been helping in the expansion and interiorization of the profession and in the development of practices different from the traditional. It is identified that the workers are working under adverse conditions that can be made explicit in the areas of formation and work relations, showing itself from the ways of hiring up to the development of routine activities in the SUAS.It is also highlighted, due to the field being new and in expansion, that its materialization as a source of reference of help to the social needs of the population still needs mediations for it to take place. The characterization of the psychologists workers of SUAS in Porto Alegre shows there are countless challenges in order to build a professional make that is commited with social rights. At last, even with the advances, implementation and regulation of SUAS is still not a complete reality in the daily work of professionals at CRASs. It is pointed out, especially, the challenge of the formation that, according to the interviewees, is still poor when it comes to prepare for working in the social sphere, lacking both references and techniques to complement the knowledge already instilled in the profession.